NEW CONVERGENCE ANALYSIS FOR COUNTABLE FAMILY OF RELATIVELY QUASI-NONEXPANSIVE MAPPINGS IN BANACH SPACES - Shehu, Y. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In this paper, we construct a new iterative scheme by hybrid methods and prove strong convergence theorem for approximation of a common fixed point of a countable family of relatively quasi-nonexpansive mappings in a uniformly smooth and strictly convex real Banach space with Kadec-Klee property using the properties of generalized f-projection operator. Our results extend many known recent results in the literature.